PERAN GURU DAYAH DALAM MENANAMKAN NILAI-NILAI KARAKTER SANTRI KELAS I DI DAYAH NURUL HUDA PAYA BAKONG - Sulaiman Sulaiman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
Dayah teachers are a major role in instilling the character values ​​of their students. The teacher is the main actor, so the attitudes and behavior of the teacher are very imprinted on the souls of the students. The character, speech and personality of the teacher become a reflection for the students. Teachers have a big responsibility in creating a generation of character and morals. However, there are still many students who have not been able to apply good character values ​​in dayah environment and outside the dayah. Therefore, the authors are interested in studying the role of the dayah teacher in instilling character values ​​for students, especially in class I Dayah Nurul Huda Paya Bakong. This study aims to determine the tips of dayah teachers in shaping the character of students starting from the methods and the supporting and inhibiting factors faced. The type of research is Field Research (field). Data collection methods are interviews (interviews), observations (observations) and documentation. The results showed that the dayah teachers in instilling character values was applied through group activities in the hope of applying discipline and responsibility characters. In addition, the application of 5s (smile, greeting, polite, patient and grateful). The solution offered to overcome obstacles in instilling character values ​​is the assignment and cooperation between teachers and parents of students.